Altitudinal patterns illustrate the invasion mechanisms of alien plants in temperate mountain forests of northern China - Zhang, Wenxin; Yin, Da; Huang, Dizhou; Du, Ning; Liu, Jian; Guo, Weihua; Wang, Renqing (Forest ecology and management, 2015)
•We compared whether altitudinal richness patterns were different between native and alien plants.•The mechanisms driving alien and native species altitudinal patterns were different.•The invasion process in mountain forests was ecological directional filtering. Alien plant invasions usually cause economic and ecological losses. Currently, exotic plants have already appeared in the understory of mountain forests that are subjected to relatively less human disturbance and are often thought of as a safe shelter for most native plants. This study aims to explore invasions patterns and underlying mechanisms in the understory of Chinese mountain forests. Sixty-three quadrats of 20m×30m were systematically set up along the elevation gradient on Mount Tai and Mount Lao, Shandong Province, China. We examined the variation in alien and native plant richness and composition along the elevation gradient to explore the invasion mechanisms of alien species in mountain forests and analyzed the relationship between alien species richness and environment factors (human disturbance, slope, aspect and canopy density) in both mountains. In contrast to native plants, which presented two different richness patterns along the elevation gradient on Mount Tai and Mount Lao, alien species richness presented a consistent decreasing tendency with increasing elevation, suggesting that mechanisms driving native and alien species richness may be different. While native plants had many specialists at high altitudes and presented an obvious change of chorological groups along the elevation gradient, most alien species distributed in high altitude areas also occurred at lower elevations. All findings indicated that the invasion process in mountain forests is from great majority of alien species that are introduced at low altitude, successively filtered out by worsening climatic conditions and decreasing anthropogenic propagule pressures along the elevation gradient, and a subset of this community spreads upward to high altitude areas. Plots with high exotic species richness where generally subject to high levels of human disturbance. We conclude that approaches of monitoring and managing alien plant species should focus on low elevation areas of mountain forests to prevent invasions of high elevation areas.